Enabling National Software Development Competitions to Identify and Enhance Student Mentor Capability in Singapore - BOESCH, Chris (Institutional Knowledge at Singapore Management University, 2014)
The authors previously developed a system to facilitate the self-directed learning and practicing of software languages in Singapore. One of the goals of this self-directed learning was to enable the creation of student mentors who would be able to assist other students during classroom sessions. Building on this work, the authors extended the platform to support the promotion and coordination of multiple programming competitions including multiple schools systems within Singapore with the goals of identifying, enabling, and mentoring students who might be better prepared to mentor their peers at their school after participating in the country wide competition. This paper covers the challenges, insights, and features that were developed in order to register and select students in Singapore to participate in coding competitions with a limited number of available competition slots.